EP904 Clinical outcomes of post-operative intraperitoneal chemotherapy for patients with early stage high grade serous ovarian cancer treated at british columbia cancer agency. (1st November 2019) - Lee, S; Albert, A; Kumar, A; Kwon, J; Tinker, A
Abstract : Introduction/Background: Intraperitoneal (IP) chemotherapy is recommended for optimally debulked stage III ovarian cancer, and its benefit for prolonging overall and progression free survival for advanced ovarian cancer was previously shown in randomized trials. In British Columbia, we extrapolated from this and have been using IP chemotherapy for stage I high grade serous ovarian cancer (HGSC) patients for the last 10 years, with IV/IP paclitaxel and IP carboplatin. We conducted a retrospective study to review the clinical outcomes of using IP/IV chemotherapy compared to IV chemotherapy for optimally debulked stage I HGSC cases. Methodology: A retrospective chart review was performed on women with early stage HGSC, who were optimally debulked at their primary surgery between 2007–2015 and received either IV or IP/IV chemotherapy post-operatively. We analyzed and compared the survival outcomes for women with stage IA–IC HGSC. Kaplan-Meier method was used to correlate chemotherapy delivery method with progression free survival (PFS) and overall survival (OS), using the statistical program R. Results: We identified 99 patients; 80 (81%) received IV chemotherapy and 19 (19%) received IP/IV chemotherapy. All patients had high grade serous tumors. Among IP/IV cohort, 2/19 (11%) dropped the IP therapy in the middle of their treatment due to abdominal pain at IP port site or hypersensitivity reaction to IV paclitaxel. 5-year PFS was 88.4% (74.5–100%) and 69.7% (58.7–82.7%) among the IP/IV and IV cohorts, respectively (p=0.549). There was a trend for higher 5-year OS for the IP/IV group; however, this did not reach statistical significance (100% vs. 71.4%; p=0.182). Conclusion: In our study, IP/IV chemotherapy with carboplatin and paclitaxel for optimally debulked stage I HGSC patients was associated with a trend for higher 5-year PFS and OS compared to IV chemotherapy, however this was not statistically significant. Larger prospective study is warranted to evaluate whether early stage HGSC truly benefits from IP/IV chemotherapy. Disclosure: Nothing to disclose.